Aerial parts of Hypericum olympicum possess antioxidant, anti-lipid peroxidation and antiglycation activity - zeb saddiqe,; Ismat Naeem,; Ghulam Abbas,; Muhammad Shahzad, (International Journal of Phytomedicine, 2014)
Objective: To investigate the crude methanol extract and solvent fractions of aerial parts of Hypericum olympicum for in vitro antioxidant, antiglycation, and anti-lipid peroxidation activity. Method: Total phenolic contents (TPC) and total flavonoid contents (TFC) of all the samples were determined by colorimetric methods. Free radical scavenging, anion scavenging, anti-lipidperoxidation and anti-glycation activities were determined using spectrophotometric analyses. Results: TPC and TFC were highest in ethyl acetate fraction (125.32 ± 1.77 mg GAE/g dE and 68.94 ± 1.03 mg QE/g dE respectively) for which strongest free radical scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) was also determined (IC50 = 121.081 ± 2.09 µg/ml). For anion scavenging, anti-lipid peroxidation and antiglycation activity strongest effect was observed for the crude methanol extract with 32.593 ± 1.95, 67.203 ± 1.48 and 42.886 ± 1.83% inhibition respectively at 500 µg/ml. The extracts were tested for cytotoxicity against NIH3T3 mouse fibroblast cells. All the extracts were non toxic at 30 µg/ml. A strong correlation was observed between TPC and radical scavenging activity while no such correlation was observed for anion scavenging, anti-lipid peroxidation and antiglycation activity. Conclusion: The polar extracts of the plant can be a good source of phytochemicals with antioxidant, anti-lipid peroxidation and antiglycation activity.